Pronouncing Inert Letters: What can we learn from undergraduate EFL students? - Rahma Agung Suci Sayekti; Mei Hardiah; Azhar Aziz Lubis (Asian TESOL Journal, 2021)
English Education students are prepared to be English teachers as one of the sources in learning activity. However, the students still mispronounced some words including ones which contain inert letters. This study aimed to find out the most frequent errors made by the English Education Students in pronouncing inert letters and the factors of the inert letters’ pronunciation errors. This study was a descriptive study which applied quantitative and qualitative approaches. The subjects of this study were 25 students of the English Education Study Program at Universitas Bengkulu. This study used recording, observation checklist, and interview as the instruments. Recording and observation checklists were used to gather subjects’ pronunciation. In order to find the factors of the pronunciation errors, an interview was conducted. The pronunciation was analysed by using pronunciation checkers, Voice Notebook and Audacity. The interview results were analysed based on factors of pronunciation accuracy. The results showed that the most frequent errors of inert letters pronunciation made by the subjects were sounded inert letter /d/ of /-nd/ by 94% and silent inert letter /a/ of /-cal-/ by 88%. The interview generated some data which shows that the factors of subjects’ pronunciation errors were native language, age, and amount of exposure to English.